2023
DOI: 10.1520/jte20220319
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Environmental Performances of Warm Mix Asphalt with Reclaimed Asphalt and Plant-Based Binder

Abstract: The environmental challenges facing society today are forcing the road construction industry to tackle the twin challenges of decreasing consumption of nonrenewable raw materials and limiting its carbon impacts. Yet, roadworks can deliver some genuine environmental benefits, along with low greenhouse gas emissions, by becoming a carbon sink. Recycling very high proportions of road construction materials and gradually incorporating bio-based products into their composition is now a proven solution. To this end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…With the requirement of energy conservation and carbon reduction, road reconstruction design become important such as the use of new materials, energy and masonry reduction design measures [1]. In 1999, Piantanakulchai took the lead in assessment of carbon emissions for a highway [2].Yue Huang measuring the carbon footprint [3].The life-cycle carbon of asphalt paving proves reducing waste is important [4,5].It is also found that context up to 34% of GHG emissions can be avoided based on current technology [6].…”
Section: Introductionmentioning
confidence: 99%
“…With the requirement of energy conservation and carbon reduction, road reconstruction design become important such as the use of new materials, energy and masonry reduction design measures [1]. In 1999, Piantanakulchai took the lead in assessment of carbon emissions for a highway [2].Yue Huang measuring the carbon footprint [3].The life-cycle carbon of asphalt paving proves reducing waste is important [4,5].It is also found that context up to 34% of GHG emissions can be avoided based on current technology [6].…”
Section: Introductionmentioning
confidence: 99%